Do monetary indicators (still) predict euro area inflation? - Boris Hofmann (Deutsche Bundesbank, 2006)
This paper assesses the performance of monetary indicators in predicting euro area HICP inflation out-of-sample over the period since the start of EMU considering a wide range of forecasting models, including standard bivariate forecasting models, factor models, simple combination forecasts as well as trivariate two-pillar Phillips Curve type forecasting models. The results suggest that monetary indicators are still useful indicators for inflation in the euro area, but that a thorough and broad based monetary analysis is needed to extract the information content of monetary developments for future inflation.
Keywords: E31; E40; C32; 330; euro area; inflation; leading indicators; money; Inflation; Prognoseverfahren; Monetärer Indikator; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten